Perceptual and Cognitive Factors for Self-Motion Simulation in Virtual Environments: How Can Self-Motion Illusions (“Vection”) Be Utilized? - Riecke, Bernhard E.; Schulte-Pelkum, Jörg (Human Walking in Virtual Environments, 2013)
How can we convincingly simulate observer locomotion through virtual environments without having to allow for full physical observer movement? That is, how can we best utilize multi-modal stimulation to provide the compelling illusion of moving through simulated worlds while reducing the overall simulation effort? This chapter provides a review on the contribution and interaction of visual, auditory, vibrational, and biomechanical cues (e.g., walking) for self-motion perception and simulation in VR. We propose an integrative framework and discuss potential synergistic effects of perceptual and cognitive influences on self-motion perception in VEs. Based on this perspective, we envision a lean-and-elegant approach that utilizes multi-modal self-motion illusions and perceptual-cognitive factors in a synergistic manner to improve perceptual and behavioral effectiveness and reduce the demand for physical (loco-)motion interfaces to a more affordable level.
Keywords: Biomedical Engineering; Cognition; Computer Imaging, Vision, Pattern Recognition and Graphics; Control, Robotics, Mechatronics; NSERC DG 2026; Riecke; Riecke_2013; Vection; Virtual environments; Walking; fullProfPromotionPackage; joerg-schulte-pelkum; locomotion; motion simulation; multi-modal vection; review; vection; vection review; virtual reality